Radiation exposure during angiographic interventions in interventional radiology – risk and fate of advanced procedures. (4th May 2022) - Kaatsch, Hanns Leonhard; Schneider, Julian; Brockmann, Carolin; Brockmann, Marc A.; Overhoff, Daniel; Becker, Benjamin Valentin; Waldeck, Stephan
Abstract: Purpose: Advanced angiographic procedures in interventional radiology are becoming more important and are more frequently used, especially in the treatment of several acute life-threatening diseases like stroke or aortic injury. In recent years, technical advancement has led to a broader spectrum of interventions and complex procedures with longer fluoroscopy times. This involves the risk of higher dose exposures, which, in rare cases, may cause deterministic radiation effects, e.g. erythema in patients undergoing angiographic procedures. Against this background, these procedures recently also became subject to national and international regulations regarding radiation protection. At the same time, individual risk assessment of possible stochastic radiation effects for each patient must be weighed up against the anticipated benefits of the therapy itself. Harmful effects of the administered dose are not limited to the patient but can also affect the radiologist and the medical staff. In particular, the development of cataracts in interventionalists is a rising matter of concern. Furthermore, long-term effects of repeated and prolonged x-ray exposure have long been neglected by radiologists but have come into focus in the past years. Conclusions: With all this in mind, this review discusses different efforts to reduce radiation exposition levels for patients and medical staff by means of technical, personal as well as organizational measures.